2010
DOI: 10.1111/j.1365-263x.2010.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dental erosion in a group of 12- and16-year-old Brazilian schoolchildren

Abstract: The results indicate that there was no correlation between dental erosion and the risk factors analysed among adolescents in Bauru/Brazil and further investigations are necessary to clarify the multifactorial etiology of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
2
21

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 24 publications
9
57
2
21
Order By: Relevance
“…Nossa avaliação identificou que 55,4% da amostra relatou dieta intermediária em relação à acidez, o que não indica associação significativa com a presença de erosão dentária (p= 0,520), corroborando com os estudos de Gurgel et al 20 , Oliveira et al 21 e Salas et al…”
Section: Discussionunclassified
“…Nossa avaliação identificou que 55,4% da amostra relatou dieta intermediária em relação à acidez, o que não indica associação significativa com a presença de erosão dentária (p= 0,520), corroborando com os estudos de Gurgel et al 20 , Oliveira et al 21 e Salas et al…”
Section: Discussionunclassified
“…The O'Brien index, which emerged in the UK, is one of the most widely used indexes for studies and surveys on the prevalence of dental erosion in children. In some of these studies, minor modifications were observed, but it could be considered a clear and comprehensive index, as it classifies the depth and extent of erosive lesions [6,27]. Further studies are still required to better understand this complex oral health problem, being a reality and concern among dentists.…”
Section: Discussionmentioning
confidence: 99%
“…It ranges from 5.5 to 65.34%; at the age of 12 years from 13 to 56.1%, at the age of 15 years from 24 to 44.2%, and at the age of 18 years from 22.2 to 55.5%. [12][13][14][15][16][17][18] Moreover, a comparison of the data from the literature regarding frequency and severity of dental erosion is hindered by the use of various scoring systems (e.g., the Eccles index, Tooth Wear index by Smith and Knight, Simplified-Tooth Wear Index, Evaluating Index of Dental Erosion, index by O'Brien, index by Lussi, index by O'Sullivan and BEWE scoring system). 19,20 In Polish youth, erosive lesions occurred at close to the same rate as those reported in the literature, aged 15 years 24.7% and aged 18 years 42.3% (evaluation according to the BEWE index).…”
Section: Discussionmentioning
confidence: 99%